. (Distillation of Cassia Leaf Oils (C. burmanii, C. zeylanicum and C. cassia) by Cohobation Method and the Identification of Oil Components - A Moestofa; Fauziah Badeges (Balai Besar Industri Agro, 1986)
The essential oils from Indonesian cinnamon leaves (Cinnamomun burmanii, Cinnamomun zeylanicum, and Cinnamomun cassia) was extracted using cohobation method. The distillation process was carried out for 3 hrs. The oil was trapped at different temperature i.e 25 degree, 70 degree and 85 degree celcius. The result showed that 70 degree celcius was the optimum temperature. The yield of oil were 0.57;1.62 and 0.31% respectively. Major components of the oils were cinnamic aldehyde and small amount of eugenol (C.burmanii), eugenol and one unidentified component (C.zeylanicum) and cinnamic aldehyde and o-metoxycinnamaldehyde (C.cassia)